(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The following article constitutes an invitation to think about the development of aboriginal groups in southernmost Patagonia facing colonizing agents of the Chilean state, since despite the existence of important investigations, the observation of interaction processes with the nationals keeps having some gaps and certain state-centered characteristics.